(untitled) (Confluenţe Bibliologice, 2020)
The paper presents the main open access resources: RI ORA USARB, IBN, National Thematic Repository (NTR Mold-LIS), DOAJ, BASE, etc., for users studying remotely during COVID-19. OPEN ACCESS is online, free, immediate access to scientiﬁc and educational resources in full (full-text) version, giving users the opportunity to both read, download, copy and use these resources for any permitted purpose, without ﬁnancial barriers, legal or technical, as well as to public display and distribute their own works, except that Open Access is not an infringement of copyright.